2001
DOI: 10.1063/1.1388169
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of hole interband tunneling in wurtzite GaN and SiC

Abstract: The time evolution of Bloch electrons (holes) moving in a constant electric field has been studied for GaN and 2H-SiC using a numerical model based on realistic band structures. The large band gap of GaN and the SiC polytypes provide much larger critical fields than in conventional semiconductors, which allows device operation at very high electric fields. At sufficiently high electric fields the carriers may change band during drift due to tunneling. GaN has a direct band gap, while the hexagonal SiC polytype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…We have found that, although this technique provides a reasonable first order formulation of the problem, particularly for transport in the c-axis direction of 4H-SiC, a more accurate description is obtained using an approach based on the time development of the probability amplitude of a Bloch electron moving in the presence of a uniform electric field. [22][23][24][25] The basis of this approach is the work of Krieger and Iafrate. 22 For simplicity, we refer to this approach as the KI model.…”
Section: Drift Modelmentioning
confidence: 99%
“…We have found that, although this technique provides a reasonable first order formulation of the problem, particularly for transport in the c-axis direction of 4H-SiC, a more accurate description is obtained using an approach based on the time development of the probability amplitude of a Bloch electron moving in the presence of a uniform electric field. [22][23][24][25] The basis of this approach is the work of Krieger and Iafrate. 22 For simplicity, we refer to this approach as the KI model.…”
Section: Drift Modelmentioning
confidence: 99%
“…This treatment, however, may not be correct when the band crossing or anticrossing exists. 29) Nilsson et al proposed a method to account for the bandto-band tunneling. 29) They employed a rigorous approach developed by Krieger and Iafrate (KI).…”
Section: Full-band Monte Carlo Simulationmentioning
confidence: 99%
“…Several approaches have been proposed to deal with this problem and their practical implementation is still under investigation. [19][20][21].…”
Section: Computational Modelmentioning
confidence: 98%